Evaluation of the impact of Tacrolimus-based immunosuppression on Heidelberg liver transplant cohort (HDTACRO): Study protocol for an investigator initiated, non-interventional prospective study. Issue 39 (25th September 2020) - Khajeh, Elias; Polychronidis, Georgios; Ramouz, Ali; Alamdari, Parnian; Lemekhova, Anastasia; Saracevic, Melisa; Ali-Hasan-Al-Saegh, Sadeq; Ghamarnejad, Omid; Majlesara, Ali; Abbasi Dezfouli, Sepehr; Nickkholgh, Arash; Weiss, Karl Heinz; et al.
Abstract: Background: Tacrolimus-based immunosuppression has resulted in enormous improvements on liver transplantation (LTx) outcomes. However, dose adjustment and medication adherence play a key role in post-transplant treatment success. The aim of the present study is to assess the trough levels and the need for adaptation of therapeutic doses in de novo LTx patients treated with Tacrolimus in the clinical routine, without any intervention to the treatment regimen. Methods and analysis: This is a pilot, prospective, exploratory, monocentric, non-interventional and non-randomized investigator-initiated study. Prospectively maintained data of 100 patients treated with various oral Tacrolimus-based immunosuppressants (Prograf or Envarsus) will be analyzed. The number of required dose adjustments of Tacrolimus formulations used in clinical routine for achieving the target trough level, Tacrolimus trough level, Tacrolimus dosing, concentration/dose ratio, routine laboratory tests, efficacy data (incl. survival, acute rejection, re-transplantation), patients therapy adherence, and infections requiring the need to reduce individual immunosuppressant dosing will be evaluated for each patient. Result: This study will evaluate the trough levels and the need for adaptation of therapeutic doses in de novo LTx patients treated with Tacrolimus in the clinical routine, without any intervention to the treatment regimen. Conclusion: The HDTACRO study will be the first study to systematically and prospectively evaluate various oral Tacrolimus-based immunosuppressants in de novo liver transplanted patients. If a difference between the therapy-subgroups is evident at the end of the trial, a randomized control trial will eventually be designed. Registration number: ClinicalTrials.gov: NCT04444817.